Five-Year Outcomes: Laparoscopic Greater Curvature Plication for Treatment of Morbid Obesity - Doležalova-Kormanova, K; Buchwald, J N; Skochova, D; Pichlerova, D; McGlennon, T W; Fried, M (Obesity surgery, 2017)
BACKGROUND: Laparoscopic greater curvature plication (LGCP) is a newer metabolic/bariatric surgical procedure that requires no resection, bypass, or implantable device. We report outcomes in a cohort of LGCP patients at 5-year follow-up. METHODS: Body mass index (BMI, kg/m2) evolution, excess weight loss (%EWL), excess BMI loss (%EBMIL), and total weight loss (%TWL) were recorded. Repeated measures analysis of variance (ANOVA) was used to assess BMI change over 5 years. Two-step cluster analysis was used to profile LGCP patients according to significant characteristics relative to successful 5-year weight loss. RESULTS: Of patients entering the study between 2010 and 2011 with complete weight data through 5-year follow-up (86.9%, 212/244), mean age was 45.8 ± 10.9 years; mean baseline BMI, 41.4 ± 5.5 (81.6% women); 58 patients (27.4%) had type 2 diabetes. Mean operative time was 69.0 min; mean hospitalization, 38 h (24-72). ANOVA indicated a significant BMI reduction out to 2 years (p < 0.001), a plateau at 3 and 4 years, and a moderate but significant BMI increase at 5 years (p < 0.01). EBMIL at 1, 2, 3, 4, and 5 years was as follows: 50.7 ± 9.1%, 61.5 ± 8.1%, 60.2 ± 7.0%, 58.5 ± 7.0%, and 56.8 ± 6.3%. At 5 years, 79.2% (168/212) of patients were successful; 20.8% (44/212) experienced a suboptimal weight outcome; mean weight regain, 9.2%. Cluster analysis identified four distinct LGCP patient profiles. Diabetes improvement rate was 65.5%. There were 12 reoperations (4.9%): 4 emergency (1.6%) and 8 (3.3%) elective. There was no mortality. CONCLUSIONS: At 5-year follow-up, LGCP proved to be safe and effective, with 56.8% EBMIL and a low rate of complications.
Keywords: dospělí; Laparoscopic greater curvature plication; Female; Laparoscopy; Gastrectomy; Operative Time; Obesity, Morbid; Bariatric Surgery; Adult; výsledek terapie; ženské pohlaví; Diabetes Mellitus, Type 2; Obesity; laparoskopie; lidé; pooperační komplikace; diabetes mellitus 2. typu; Treatment Outcome; následné studie; Reoperation; Weight Loss; reoperace; gastrektomie; Follow-Up Studies; Male; Postoperative Complications; Diabetes; bariatrická chirurgie; index tělesné hmotnosti; hmotnostní úbytek; délka operace; lidé středního věku; mužské pohlaví; LGCP; Body Mass Index; Middle Aged; morbidní obezita; Humans